A terceirização de serviços na UFMT como expressão do projeto de desmonte do ensino superior público - Kitagawa, Adriana Aparecida do Vale (2018)
In this work, we chose the phenomenon of outsourcing services in UFMT as an object of research, with the objective of analyzing the socioeconomic impacts of outsourcing in the UFMT, from 2008 to 2016. We identified that at the end of 2016, there were 23 contracts in force between UFMT and outsourced service providers, being executed by 13 different companies. A total of 915 workers provided daily services on the five subsidiaries of the institution. In addition to the continuous services, which can not be interrupted without prejudice to the institution, the UFMT bid a wide variety of other services of a temporary and transitional nature during the period studied. We verified that the financial cost of these contracts had a constant evolution, impacting on the budget of the institution. Expenses with outsourcing of continued services also increased proportionately above the expenses with actual personnel in the same period. Despite the government's justification for outsourcing services to reduce spending, the significant increase in costs of these contracts deserves special attention. During the period studied, technical positions were abolished and replaced by outsourced service providers. The extinction of public positions still in use favors the extension of the outsourcing and weakens the public service. The number of administrative technicians in education did not follow the constant evolution in the number of students enrolled, in addition, the impact of outsourcing on public tenders was also verified. The study showed that the public examinations for technical positions carried out by the university did not represent an increase of vacancies, on the contrary, they only dealt with fill vacancies. Public higher education institutions have also suffered from the budget constraint, with severe reduction of investments and costing, contributing to the scrapping of these institutions. The discourse is spread that the IFES are expensive, with little return, even more when compared to the private institutions. This is the panorama that presents itself for the public university: extinction of public positions, extension of the outsourcing and scrapping of the public universities. This seems to be the recipe for a deliberate project to meet the demands of capital, without concern for the future social consequences of these measures.